motivasi intrinsik, analisis pek Peran Motivasi Intrinsik dalam Memoderasi Pengaruh Analisis Jabatan, Beban Kerja, dan Kompetensi terhadap Kinerja Karyawan (Studi Empiris Pegawai Kecamatan di Seluruh Kabupaten Kuningan): Analisis Pekerjaan, Beban Kerja, dan Kompetensi terhadap Kinerja Karyawan - Lina Herlina; Dikdik Harjadi; Yanneri Elfa Kiswara Rahmantya (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
The problem in this research is motivated by the decline in the performance of sub-district employees in Kuningan Regency in the period 2021–2024, which is reflected in the decline in the value of the Individual Performance Indicator (IKI) as well as the results of the pre-survey which showed weaknesses in the quality aspect. work, punctuality, cooperation, and efficiency cost. Study This This For Analysis influence analysis This study examines the relationship between position, workload, and competence on employee performance, and examines the role of intrinsic motivation in moderating this relationship. The research method used was a survey with a descriptive analysis type and a quantitative approach. The sampling technique used was probability sampling with a random sampling method. example, with amount sample as many as 201 employee ASN Subdistrict throughout Kuningan Regency. Data collection techniques were conducted through questionnaires with an interval scale of 1–10 and documentation. Data analysis included descriptive analysis, classical assumption tests, and moderated regression analysis. The results of the study showed that: (1) job analysis had a positive and significant effect on employee performance, (2) workload had a negative and significant effect on employee performance, (3) competence had a positive and significant effect on employee performance, (4) intrinsic motivation had a positive and significant effect on employee performance, (5) intrinsic motivation was able to moderate influence analysis Position on employee performance, (6) Intrinsic motivation is able to weaken the negative influence of workload on employee performance, and (7) intrinsic motivation is able to strengthen the influence of competence on employee performance. This finding emphasizes the important role of intrinsic motivation in increasing the effectiveness of human resource management in government environments